Quality of stingless bee mandaçaia (Melipona quadrifasciata) honey under different storage conditions - Bernhardt, Pedro Henrique Peterle; Arboitte, Miguelangelo Ziegler; Duarte, Maisa Benedete; Melo, Amanda Fonseca de; Castellen, Patrícia (Revista de Ciências Agroveterinárias, 2025)
The advancement in the commercialization of honey from native bees implies the need to develop applied research, for better conservation after its harvest. Therefore, the objective of the work was to analyze the quality of mandaçaia honey (Melipona quadrifasciata) under different storage conditions. The experimental design used was a 2x3 factorial, consisting of factor A “light” (with and without) and factor B “temperature” (5 °C, 20 °C and 35 °C), where a sample of 210 mL of honey was collected and subjected to analysis of physical-chemical-biological parameters (free acidity, ash, color, hydroxymethylfurfural (HMF), pH, humidity and CFU count of molds and yeasts). Then, the sample was divided into 6 other subsamples, which were subjected to treatments for 72 hours and then underwent analysis, generating seven treatments in total. The interaction of the results between the factors was tested at 5% probability, using the ANOVA analysis of variance, when no interaction was found, the light factor and the temperature factor were separated and analyzed by the Tukey test at 5% probability and an analysis of regression. The HMF levels observed were close to zero in all treatments, ash and moisture contents did not interact between the factors, and free acidity, pH, color and number of CFU of molds and yeasts showed an interaction between the factors. In all analyzes it was observed that temperature has greater influence and significance in maintaining honey parameters than light, demonstrating that for greater stability of honey parameters, it must be stored at 5 °C, regardless of the presence or absence of light.